Memaknai Tanggung Jawab Gereja Terhadap Kaum Marginal Perkotaan Melalui Pemikiran Emmanuel Levinas - Randing Rante Toding; Imanuel Teguh Harisantoso (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
This study purpose to analyze the ethical responsibility of the church towards marginalized groups based on the ideas of Emmanuel Levinas. This research is qualitative-analytical using the library research method. This research shows that Emmanuel Levinas' thoughts regarding ethical responsibility can be a basis for the church to respond to the existence of marginalized people in urban areas. The ethical responsibility in question is the responsibility to maintain humanitarian actions, acknowledge their existence, provide attention and protect their rights as human beings. In this case, the church as an institution has a great ethical responsibility towards the marginalized, especially in the context of socio-economic justice.